Current Guidelines for the Treatment of Arterial Hypertension in Patients with Diabetes Mellitus and Chronic Kidney Disease - T. Yu. Demidova; O. A. Kislyak (Рациональная фармакотерапия в кардиологии, 2021)
The current understanding of the management of patients with diabetes mellitus (DM) based on the concept of the cardiovascular continuum involves not only the prevention and treatment of cardiovascular diseases (CVD), but also the prevention and treatment of chronic kidney disease (CKD). The fact is that patients with DM and CKD represent a special group of patients with a very high risk of CVD and cardiovascular mortality. Such patients require early diagnosis and timely identification of risk factors for the development and progression of CKD for their adequate correction. Arterial hypertension, along with hyperglycemia, is the main risk factor for the development and progression of CKD in patients with diabetes. In this regard, the choice of antihypertensive therapy (AHT) in patients with diabetes is of particular importance. The basis of AHT in diabetes and CKD is the combination of a blocker of the renin-angiotensin-aldosterone system (an angiotensin-converting enzyme inhibitor [ACE inhibitor] or an angiotensin II receptor blocker [ARB]) and a calcium channel blocker (CCB) or a thiazide / thiazide-like diuretic. The task of the performed AHT is to achieve the target level of blood pressure (BP). At the same time, the optimal blood pressure values in patients with diabetes and CKD are blood pressure values in the range of 130-139/70-79 mm Hg. If the target blood pressure is not achieved, it is necessary to intensify antihypertensive therapy by adding a third antihypertensive drug to the therapy: CCB or a diuretic (thiazide / thiazide-like or loop). In case of resistant hypertension, it is necessary to consider the possibility of adding antagonists of mineralocorticoid receptors, other diuretics or alpha-blockers to the conducted AHT. Beta-blockers can be added at any stage of therapy if the patient has exertional angina, a history of myocardial infarction, atrial fibrillation, and chronic heart failure. The need to normalize blood pressure parameters by prescribing combined antihypertensive therapy in patients with diabetes and CKD is explained by a decrease in renal and cardiovascular risks, and, therefore, a decrease in the risk of mortality in this cohort of patients.